Pengaruh Pendekatan Saintifik Berbantuan Asesmen Portofolio Terhadap Prestasi Belajar IPA Ditinjau dari Gaya Kognitif - Made Ayu Pransisca; Abdul Alim (Lembaga Bale Literasi, 2025)
This research aims to determine the effect of a scientific approach assisted by portfolio assessment on science learning achievement in terms of students' cognitive styles. The research population was class IV students at SD Gugus V Cakranegara, totaling 239 people. The sample was taken using a random sampling technique totaling 68 people. This research is quasi-experimental with a 2x2 factorial design. Science learning achievement data was collected using learning achievement tests and cognitive style was collected using GEFT. Data analysis used Anava AB with the F test. The results showed that: (1) There was a difference in science learning achievement between students who took learning using a scientific approach assisted by portfolio assessment and students who took learning with a conventional approach (FA calculated = 10.768, with p < 0.05), (2) There was an interaction effect between the implementation of a learning approach with a cognitive style on science learning achievement (FA calculated = 50.840, with p < 0.05), (3) There was a difference in achievement science learning between students who took learning with a scientific approach assisted by portfolio assessment and students who took learning with a conventional approach in students with a field independent cognitive style with Qcount = 10.413 and p < 0.05, (4) There was a difference in science learning achievement between students who took learning with a scientific approach assisted by portfolio assessment and students who took learning with a conventional approach among students with a field dependent cognitive style with Qcount = 3.85 and p